Analisis Hubungan Interpersonal Antara Guru Dan Orang Tua Murid Penyandang Autisme - Ardhi, Kuntjoro Nuril (Universitas Brawijaya, 2022)
This study takes the problem of the need for cooperation of teachers and parents in the learning process of children. In children with special needs, the role of teachers and parents because they are the 'pillars' in children's education, especially in this study is a child with autism needs. The purpose of this study is to describe, illustrate, and understand what kind of interpersonal relationship that exists between teachers and parents of students with autism in SLB Negeri 3 Jakarta. This research uses qualitative research type with descriptive method, data completion technique using in-depth interview technique and documentation study. The results of this study illustrate the relationship between teachers and parents of students with autism in SLB Negeri 3 Jakarta run well and relationships conducted with the aim that children's information both at school and at home can be delivered in both directions. Teachers and parents choose to conduct self-disclosure so that information can be exchanged properly.